Supervision of the Implementation of Justice during the Caliphate of the Rashidun from the Perspectives of History and Socio-Politics - Marwah, Andi; Zulkifli, Zulkifli; Halim, Abdul; Asni, Asni (al-Rasῑkh: Jurnal Hukum Islam, 2025)
Supervision of judicial proceedings during the era of the Rashidun Caliphate was a crucial aspect influencing social justice and the sustainability of early Islamic legal systems. The aim of this study is to conduct a comprehensive analysis of the mechanisms of supervision and the challenges faced by caliphs in ensuring justice during this period. The research methodology employs a qualitative descriptive-analytical library review, examining primary and secondary sources from classical and contemporary literature. Findings indicate that supervision was systematically implemented through the roles of caliphs, community reports, and direct oversight, despite challenges related to geography, limited human resources, and varying interpretations of law. The principles of power separation and the Ijtihad of caliphs actively strengthened the supervision mechanisms, while socio-political dynamics influenced their application and continuation. This study enriches the historical study of Islamic law and offers valuable insights regarding the relevance of past supervision practices in strengthening justice and integrity in contemporary judicial systems.